Study on Ammonia and Suspended Solids Removal from Leachate using Aerated Electrocoagulation (Aluminium Electrodes) Under the Influence of Aeration Rate, Current Density and pH - SHOHAIMI, NURUL SYAHIDAH; MOHD ZIN, NUR SHAYLINDA (Recent Trends in Civil Engineering and Built Environment, 2022)
This research was conducted to investigate the performance of aluminium electrode in aerated electrocoagulation process in removing chemical oxygen demand (COD), biochemical oxygen demand (BOD), colour, pH, suspended solid, turbidity and ammonia from Simpang Renggam Landfill leachate. Review the removal of ammonia and suspended solid from stabilized leached by using aerated electrocoagulation (aluminium electrodes) under the influence of aeration rate, current density, and pH from previous papers were observed in this study. Through a reviewed study, the most effective range for the electrocoagulation process for optimization of current density in removal ammonia was expected at range between 30 A/m2 to 600 A/m2 which give the highest percentage of removal ammonia by using aerated electrocoagulation (AEC) process from range 19.8% up to 71.01% while for suspended solid it was expected at range between 30 A/m2 to 500 A/m2 which give the highest percentage of removal suspended solid by using AEC process from range 25% to 96%. Then, the optimum pH for ammonia removal based on previous studies was expected at range from pH 5 to pH 9.6 which give the highest percentage of removal ammonia by AEC process from range 16.0% to 85.5%. Besides, the optimum pH for suspended solid was expected at range from pH 4 to pH 7 which give the highest percentage of removal suspended solid by AEC process from range 73% to 89%.  Based on previous studies, the optimum aeration rate in removal ammonia was expected at range from 0.25 L/min to 6 L/min with the percentage of removal ammonia by using AEC process at range 10% to 95.7%. This indicated that aerated electrocoagulation treatment process able to reduce the level of pollutants in the waste.